Factors affecting the choices of coping strategies for climate extremes: The case of farmers in the Nile Basin of Ethiopia - Deressa, Temesgen T.; Ringler, Claudia; Hassan, Rashid (International Food Policy Research Institute, 2010)
This study adopted the multinomial logit model to analyze factors affecting the choice of coping strategies in response to climate extreme events for the Ethiopian Nile River Basin. Results from the multinomial logit model show that different socioeconomic and environmental factors affect coping with climate extreme events. Factors that positively influence coping include education of the head of household, gender of household head being male, farm income, livestock ownership, access to extension for crop and livestock production, farmer-to-farmer extension, temperature, ownership of radio, and better-quality house. Thus, to increase coping with covariate shocks, such as climate extreme events, policies should encourage income generation and asset holding (especially livestock), both of which will support consumption smoothing during and immediately after harsh climatic events. Moreover, government policies should focus on developing institutions that enhance access to education and extension services.